Playing with Signs : a Semiotic Interpretation of Classic Music. - Agawu, V. Kofi (Victor Kofi) (Princeton legacy library., 2014)
Of all the repertories of Western Art music, none is as explicitly listener-oriented as that of the late eighteenth and early nineteenth centuries. Yet few attempts to analyze the so-called Classic Style have embraced the semiotic implications of this condition. Playing with Signs proposes a listener-oriented theory of Classic instrumental music that encompasses its two most fundamental communicative dimensions: expression and structure. Units of expression, defined in reference to topoi, are shown here to interact with, confront, and merge into units of structure, defined in terms of the r.